Peran Reward dan Punishment Dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran IPS di Kelas VIII SMP Negeri 17 Bandung - Prastiwi, Davina Putri; Sundawa, Dadang; Muthaqin, Dwi Iman (Peneliti.net, 2024)
The Role of Reward and Punishment Methods in Increasing Student Learning Interest in Social Studies Learning Class VIII SMP Negeri 17 Bandung. The purpose of this study is to analyze the role of reward and punishment methods in increasing students' interest in social studies learning in grade VIII SMP Negeri 17 Bandung. This research uses a qualitative approach with a descriptive method. Data were collected using observational techniques, interviews, and documentation studies. The results showed that the reward and punishment method strategies in increasing interest in learning have been implemented appropriately and wisely, both from planning, implementing, and evaluating learning. The types of rewards and punishments given vary to avoid boredom. The application of reward and punishment methods in social studies learning in grade VIII SMP Negeri 17 Bandung is able to increase students' interest in social studies learning, which is shown by positive changes from within students.